Experimental study on heave damping due to the heave plate addition on the SPAR keel. Issue 1 (February 2021) - Murdjito,; Ali, B; Ardhianutama, F; Djatmiko, E B; Syahroni, N; Mulyadi, Y; Riyanto, R D; Prastianto, R W; Handayanu,; Rochani, I
Abstract: Recent years have shown the increasing number of SPAR offshore floating platforms built and delivered worldwide. This eventually is strongly related to the generic potential of such platforms, in term of economy and performance aspects, especially for the operation in deep water. For operation in harsh sea environment previous SPAR investigations suggested the addition of heave plate on its keel to enhance the heave motion quality. This paper reports an experimental study conducted on SPAR model, scaled 1: 125 from the full size, installed with a heave plate sized 1.3 of hull diameter. Results of the study demonstrate the additional of heave plate may reduce the heave reaction force due to wave excitation approximately 35% in comparison with that without heave plate. This in turn leads to the decreasing of heave response by as much as 54%. Evaluations suggest the reductions in heave reaction force and response are induced by the escalation of heave damping in the order of 49% generated by the heave plate. The experimental results are well verified by the outcomes of computations based on analytical method and strip theory.